Polymorphism of the XRCC3 gene and risk of gastric cancer in a Kashmiri population. Issue 3 (May 2015) - Bashir, Haamid; Majid, Sabhiya; Hamid, Rabia; Farooq, Rabia; Wani, Hilal A.; Shoib, Sheikh; Bhat, Arief A.
<x xml:space="preserve">Abstract</x> DNA repair plays a critical role in protecting the genome of the cell from the insults of cancer-causing agents. Genetic polymorphisms in DNA repair genes may influence individual variation in DNA repair capacity, which may be associated with the risk of developing cancer. Inherited polymorphisms of DNA repair genes may contribute to variations in DNA repair capacity and genetic susceptibility to different cancers. The X-ray repair complementing defective repair in Chinese hamster cells 3 (XRCC3) gene is a member of the RAD51 gene family. It encodes an important protein that functions in the homologous recombination repair of a DNA double-strand break. For gastric cancer, the importance of mutations in mismatch repair genes has been well documented, but less is known about other DNA repair pathways in gastric carcinogenesis. In this study, we have focused on the XRCC3 gene, involved in homologous recombinational repair. The Kashmir valley has an increased incidence of gastric cancer and its etiology has not been understood fully as yet. As the Kashmiri population is ethnically and demographically different from that in other parts of the world, the aim of this study was to determine whether a single nucleotide polymorphism of the XRCC3 gene (Thr241Met) of exon 7 can influence the risk of gastric cancer in the population. As many as 80 histopathologically confirmed gastric cancer cases and 70 healthy controls, age, sex, and ethnicity matched for known genotypes of XRCC3 exon 7 were studied. We genotyped for this variant using PCR-restriction fragment length polymorphisms. The XRCC3 genotype and allele frequencies were not significantly different between cases and controls (P=0.92 for the genotype; P=0.72 for the allele). The XRCC3 241Met allele frequency (6.6%) was significantly lower in healthy Kashmiri controls than reported previously in healthy US White controls (38.9%). Compared with the XRCC3 241Thr/Thr genotype, the variant XRCC3 241Thr/Met and Met/Met genotypes were not associated with an increased risk of gastric cancer (adjusted odds ratio=1.19; 95% confidence interval=0.44–3.18). These findings suggest that polymorphisms of XRCC3 Thr241Met may not play a role in the etiology of gastric cancer. Further studies with a larger number of participants and simultaneous measurement of different polymorphisms in DNA repair genes in the same pathway are needed.